Effect of Weed Management Practices on Weed Dynamics, Yield and Yield Attributes of Maize in Chitwan, Nepal - Bastola, Arjun (Journal of the Plant Protection Society, 2024)
Field trial was conducted for the assessment of different weed management practices in farmer’s field of Chitwan, Nepal in randomized complete block design using five treatments replicated four times in summer season of 2022. Weed density and weed dry weight were taken at 30, 60 and 90 days after sowing (DAS) of maize, and yield and yield attributes were recorded at the time of maize harvesting. The result revealed that at 30 DAS both weed density and weed dry weight were lower and both weed control efficiency and weed control index were higher in both tembotrione 42% SC and atrazine 50% SC. But at 60 DAS and 90 DAS weed density, weed dry weight, weed control efficiency and weed control index were found higher in two-hand weeding than other treatments. Days to silking were later in weedy check than other. Ear diameter, kernels per rows, thousand kernels weight and shelling percentage of maize was seen significantly highest in two-hand weeding and lowest in weedy check. Significantly highest grain yield was recorded in two-hand weeding followed by tembotrione 42% SC, atrazine 50% SC and one-hand weeding. So, two-hand weeding and tembotrione 42% SC could be recommended for effective weed management and higher yield of maize.